2021
DOI: 10.3390/ijms222212223
|View full text |Cite
|
Sign up to set email alerts
|

A Yeast-Based Repurposing Approach for the Treatment of Mitochondrial DNA Depletion Syndromes Led to the Identification of Molecules Able to Modulate the dNTP Pool

Abstract: Mitochondrial DNA depletion syndromes (MDS) are clinically heterogenous and often severe diseases, characterized by a reduction of the number of copies of mitochondrial DNA (mtDNA) in affected tissues. In the context of MDS, yeast has proved to be both an excellent model for the study of the mechanisms underlying mitochondrial pathologies and for the discovery of new therapies via high-throughput assays. Among the several genes involved in MDS, it has been shown that recessive mutations in MPV17 cause a hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 82 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…In a yeast model with SYM1 mutation, the ortholog of the human MPV17, several molecules were identified that could increase the dTTP pool and mtDNA stability. Interestingly, some of these molecules affect ergosterol levels and therefore could work through increasing the permeability of mitochondrial membranes [110]. There is an ongoing phase 2 clinical trial to evaluate supplementation of deoxycytidine and deoxythymidine in children with mtDNA depletion syndromes (including MPV17 deficiency) (https://clinicaltrials.gov/ct2/show/NCT04802 707, accessed on 8 May 2022).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…In a yeast model with SYM1 mutation, the ortholog of the human MPV17, several molecules were identified that could increase the dTTP pool and mtDNA stability. Interestingly, some of these molecules affect ergosterol levels and therefore could work through increasing the permeability of mitochondrial membranes [110]. There is an ongoing phase 2 clinical trial to evaluate supplementation of deoxycytidine and deoxythymidine in children with mtDNA depletion syndromes (including MPV17 deficiency) (https://clinicaltrials.gov/ct2/show/NCT04802 707, accessed on 8 May 2022).…”
Section: Therapeutic Strategiesmentioning
confidence: 99%
“…Very recently, it was shown that the yeast mitochondria of sym1Δ mutant displayed a significant decrease in the levels of all the dNTPs, suggesting that, as in the Mpv17 −/− mouse and in MPV17 -deficient human fibroblasts, the instability of mtDNA in sym1∆ yeast mitochondria is associated with a decrease in dNTPs levels, providing strong evidence that the cause of the mtDNA deletion/depletion in Sym1 deficient cells is a shortage of precursors for DNA synthesis [ 40 ]. Furthermore, it was demonstrated that the nucleotide reduction is not limited to the mitochondrial compartment but is instead extended to the entire cell compartment.…”
Section: Genes Studied In Yeastmentioning
confidence: 99%
“…The whole-cell dNTP pool decrease could be due to a reduced ATP production caused by the OXPHOS impairment; however, OXPHOS defect and mtDNA instability occur independently in sym1Δ yeast cells [ 110 ]. Another tempting explanation links this dNTP shortage to the Sym1 proposed function, as TCA cycle intermediates homeostatic control [ 40 ]. Indeed, it was previously reported that the OXPHOS defect of sym1Δ strain was rescued by the overexpression of mitochondrial transporters of TCA intermediates ( YMC1 and ODC1 ), or by the supplementation of different amino acids (glutamate, aspartate, glutamine, or asparagine) produced from TCA intermediates and all precursors of nucleotides synthesis [ 110 ].…”
Section: Genes Studied In Yeastmentioning
confidence: 99%
See 2 more Smart Citations